2022
DOI: 10.1186/s12875-022-01653-7
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy use in primary care: a qualitative study with general practitioners

Abstract: Background Skin assessments constitute a significant proportion of consultations with family physicians (commonly called general practitioners or GPs in the UK), and referrals to hospital dermatology departments have risen significantly in recent years. Research has shown that dermoscopy use may help GPs to assess and triage skin lesions, including suspected skin cancers, more accurately. However, dermoscopy is used by a small minority of GPs in the UK. Previous questionnaire studies have aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…Our results align with previous studies assessing the specificity and sensitivity of GPs for melanoma screening [ 14 , 29 ]. Although we found similar results when assessing the diagnostic accuracy of macroscopic and dermoscopic evaluation separately, previous studies reported that combining naked-eye and dermoscopic assessment can increase diagnostic accuracy [ 19 , 30 , 31 , 32 , 33 ]. However, as the first step of non-specialist involvement in screening, implementing macroscopic assessment of the whole skin surface of the patients in daily practice would be more reasonable than implementing dermoscopic assessment, as it has no special asset requirements [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 80%
“…Our results align with previous studies assessing the specificity and sensitivity of GPs for melanoma screening [ 14 , 29 ]. Although we found similar results when assessing the diagnostic accuracy of macroscopic and dermoscopic evaluation separately, previous studies reported that combining naked-eye and dermoscopic assessment can increase diagnostic accuracy [ 19 , 30 , 31 , 32 , 33 ]. However, as the first step of non-specialist involvement in screening, implementing macroscopic assessment of the whole skin surface of the patients in daily practice would be more reasonable than implementing dermoscopic assessment, as it has no special asset requirements [ 31 , 33 ].…”
Section: Discussionsupporting
confidence: 80%
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%
“…[16,17] Badania pokazują, że koszt zakupu własnego dermatoskopu może być barierą dla wielu lekarzy rodzinnych, jednak gdy urządzenie jest dostępne w miejscu pracy odsetek lekarzy chętnych do szkolenia i używania dermatoskopii w codziennej diagnostyce rośnie. [18].…”
Section: Aktualny Stan Wiedzy Czerniak Złośliwyunclassified